Evaluation of tensile properties of natural sand particle reinforced polymer composite - Kong, Pu Wei (2013)
Nowadays, reinforced plastic composites are replacing metals which are being used for many years. This is due to the fact that reinforced plastics have high strength to weigh ratio, low cost compared to metals, and high resistance to corrosion. However, the production of the composites nowadays is very challenging to meet the market requirement. Though natural sand is abundant in the world and very cheap, there are not many studies regarding the mechanical properties of natural sand particle reinforced composites. The objective for this thesis is to determine the tensile properties of natural-sand particle reinforced polymer composite and to validate the experimental results against theoretically calculations. To perform this, first we needed to prepare samples.The samples were prepared with mix and heat method. A few samples were produced by varying the sand weight percentage in the composites. Six samples were produced with 5%, 10%, 15%, 20%, and 30% sand percentage by weight. Next, the samples were tested with 3-Point Bending Testing Machine and Universal Tensile Testing Machine to obtain the respective value of flexural and tensile properties of the composite samples.After that, the values obtained were compared against theoretical values which were obtained from calculation.The results obtained were in fair agreement with the experimental values. Both experimental values of the elastic modulus and ultimate tensile strength were relatively low compared to theoretical ones. There may have a lot of reason for this, but we believe that the primary reason is due to the fact that there is a critical point where the elastic modulus or ultimate tensile strength is at its lowest. In conclusion, the result is satisfying as the trend is similar although the values between theoretical and experimental are not exactly same.